Vista of Metz, France - Published by Foriss'er | G (Wikimedia Commons, 1919)
Carte postale ancienne issue de Wikimedia Commons. Titre: Vista of Metz, France. Photo postcard is an bird's eye view of the Skyline of Metz, France. Clearly Visible are the steeples of three churches
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; Histoire Locale; Wikimedia Commons; église; Carte postale